The Effects of Sugammadex on Vitamin D Levels in Rabbits Under General Anesthesia - Tuğba Hünerel; Hatice Betül Altınışık (Galenos Yayinevi, 2019)
Objective:Sugammadex is a widely used anesthetic agent for reversing of the non-depolarizing block. It reduces blood levels of steroid compounds by encapsulation. The aim of this study was to investigate the effect of sugammadex on the blood levels of vitamin D levels, which has a steroid structure.Materials and Methods:A total of 15 adult male New Zealand white rabbits weighing 2-2.5 kg were randomized into three groups according to decurarization: Group S [sugammadex (16 mg/kg), n=5], group N [neostigmine (0.05 mg/kg), n=5], group C (control group, n=5). Vitamin D levels from venous blood were measured at baseline, 20 minutes and 24 hours after general anesthesia.Results:Mean ± SD vitamin D levels before anesthesia, 20 minutes and 24 hours after anesthesia were 4.42±0.60 ng/mL, 4.93±0.72 ng/mL, and 4.66±0.94 ng/mL for group S, 4.92±0.45 ng/mL, 5.02±0.41 ng/mL, and 5.41±0.56 ng/mL for group N, and 5.15±0.82 ng/mL, 4.57±1.10 ng/mL, and 5.21±1.05 ng/mL for group C, respectively. There were no significant differences in the mean vitamin D levels between the groups at baseline, 20 minutes, and 24 hours.Conclusion:Contrary to expectations, it was found that sugammadex did not have a statistically significant effect on blood levels of vitamin D.